The Christmas tree farm - Gilmore, Laurie (Gilmore, Laurie. Dream Harbor series, 2024)
"Kira North hates Christmas. Which is unfortunate since she just bought a Christmas tree farm in a town that's too cute for its own good. Bennett Ellis is on vacation in Dream Harbor taking a break from his life in California. And most importantly, taking a break from his latest run of disastrous dates. After a run in with Kira in her fields, Ben has no intention of offering to help the grumpy owner set up her tree farm, despite the fact she's clearly got no idea what she's doing. Kira knows she should stop being so stubborn, but her farm is not all cute and cozy like people always show on social media, it's borderline dangerous with no heating, and she'd rather no one saw it. But somehow fate finds Ben at Kira's farm once more, and as Kira watches him swing an ax at the first tree, she finds herself appreciating his strength and questionning why she refused help in the first place"--